Educators shape elementary students' moral values for Indonesia's Golden 2045 - Aditya Tri Saputra; Fadel Muhammad Haikal; Mohamad Reza Wibowo; Syifa Azzahra Erina Putri (Institute of Computer Science (IOCS), 2023)
Schooling is one of the most important variables that may shape and drive the development of an individual's moral and character traits, particularly during the period of schooling known as elementary education. The instillation of moral principles and a good character in primary school kids is a very significant part of the attempt to fulfill the Golden Indonesia vision 2045. Educators play a very important role in this. This research intends to explain why the role of educators is highly important in shaping the moral values and character of students, as well as how it can contribute to the goals of Indonesia Emas 2045. The study also wants to explain why this role is very crucial in developing the moral values and character of students. The method of searching the existing literature and conducting an analysis of the collected data led to the conclusion that educators play a role in the formation of moral and character in basic education in the following ways: (1) laying the groundwork for moral and character development; (2) fostering the development of positive values; and (3) fostering the growth of robust personalities. As a result of their significant role, educators have the power to assist in the development of young people who possess high moral standards, solid character, and the capacity to contribute to the realization of the Golden Indonesia 2045 vision.